2007
DOI: 10.1111/j.1751-1097.2007.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Melanogenesis is a Risk Factor for Oxidative DNA Damage— Study on Cultured Melanocytes and Atypical Nevus Cells

Abstract: Melanin synthesis is an oxygen-dependent process that acts as a potential source of reactive oxygen species (ROS) inside pigment-forming cells. The synthesis of the lighter variant of melanin, pheomelanin, consumes cysteine and this may limit the capacity of the cellular antioxidative defense. We show that tyrosine-induced melanogenesis in cultured normal human melanocytes (NHM) is accompanied by increased production of ROS and decreased concentration of intracellular glutathione. Clinical atypical (dysplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 35 publications
2
66
0
Order By: Relevance
“…Persons with fair skin, a poor ability to tan and a freckled complexion double their risk for melanoma [74]. In those persons with fair skin and red hair, specific mutations at the MC1R gene are responsible for the switch from eumelanin to phaeomelanin, inducing increased oxidative stress and higher risk of melanoma [35,36]. In a similar manner, it was demonstrated that recessive yellow mice with loss-of-function MC1R were developing more invasive melanoma than their albino counterparts [75].…”
Section: Melanomamentioning
confidence: 56%
See 1 more Smart Citation
“…Persons with fair skin, a poor ability to tan and a freckled complexion double their risk for melanoma [74]. In those persons with fair skin and red hair, specific mutations at the MC1R gene are responsible for the switch from eumelanin to phaeomelanin, inducing increased oxidative stress and higher risk of melanoma [35,36]. In a similar manner, it was demonstrated that recessive yellow mice with loss-of-function MC1R were developing more invasive melanoma than their albino counterparts [75].…”
Section: Melanomamentioning
confidence: 56%
“…Although cysteinylDOPA was suggested to have a role in scavenging ROS [34], this is only an intermediary in the chemical reaction, and phaeomelanin would behave as a unique 'living' polymer and biocatalyst that may grow by simple exposure to monomer building blocks and then trigger autoxidative processes [33]. This increased risk of oxidative damage with increased phaeomelanin production could potentially put nevus cells, recognized precursors of melanoma, at risk of oxidative damage [35,36]. To date, there is no clear view about whether eumelanin has a pro-oxidant or antioxidant capacity and this issue remains controversial.…”
Section: The Redox Status Of Melanocytes Depends On the Skin Colormentioning
confidence: 99%
“…Hypermelanosis induced by UVR has been previously suggested to associate with melanomageneis, although the role of UVR in the development of melanoma is complicated since melanogenesis may depend on several factors such as skin type, genetic influence, the extent of sun exposure (e.g., intensity, timing and duration of UVR) and types of moles representing disturbed melanin synthesis (Parvel et al, 2004;Rass & Reichrath, 2008;Tran et al, 2008). Melanin has been well recognized for its photoprotective properties, although melanogenic intermediates can be phototoxic and UVR-dependent elevated melanogenesis could thus be biologically harmful, genotoxic and contributed to melanoma initiation, especially in lightly pigmented individuals (Brenner & Hearing, 2008;Smit et al, 2008;Takeuchi et al, 2004;Yamaguchi et al, 2006). The desire to have fair or tanned skin depends on different cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The ROS/ RNS primarily generated by UVA radiation can cause direct deleterious chemical modifications to cellular components including lipids, proteins and, especially DNA, which can eventually initiate melanomagenesis (Cotter et al, 2007). A disturbance in the antioxidant network and an accumulation of oxidative products were also demonstrated in skin tissues of melanoma skin cancer and in melanocytes from atypical nevi (Sander et al, 2003;Smit et al, 2008). Moreover, the presence of high levels of RNS, in particular nitric oxide (NO), and nitrosative products in cutaneous melanoma has been observed to be correlated with poor prognosis of patients and contributed to melanoma invasiveness (Chin & Deen, 2010).…”
Section: Uv-induced Melanogenesis and Melanomagenesismentioning
confidence: 99%
“…Melanocytes are highly sensitive to oxidative stress, so that they die rapidly under exogenous and inflammatory oxidative stress. 28,29 Environmental stressors such as UV radiation but also psychosocial stress generate oxidative stress and promote mutagenesis (Fig. 1).…”
Section: Neuroendocrine-immune Interaction and Skin Cancer Control: Tmentioning
confidence: 99%